Diskursus Ayat-ayat Karakteristik Kepemimpinan dalam Pendidikan Islam (Kajian Surat At-Taubah Ayat 71 dan Al-Maidah Ayat 57) - Kusniawan, Wahyu; Zaini, Hilmi Abdussalam; Saputra, Rio; Hillay, Ammar (ALSYS, 2021)
Efforts to improve Islamic education are certainly very closely related to the quality of leaders who have a strategic position as well as being at the forefront of leading the direction of Islamic education itself. Therefore, it is necessary to have criteria and characteristics in Islamic education leadership. The Qur'an as the main guideline for Islamic society has given various signs relating to Islamic leadership. In this journal, we will examine the messages, wisdom and signs contained in the Qur'an Surah At-Taubah verse 71 and Al-Maidah verse 57. Through descriptive analysis methods, this article tries to uncover messages and wisdom that provide solutions related to Islamic education leadership characteristics. So that it is expected to be able to provide a clear description, criteria and profile when choosing a leader or being given the mandate as a leader in an educational institution or other agency.